MEMORIAL LEGISLATION OF EASTERN EUROPEAN COUNTRIES: BETWEEN ETHNOPOPULISM AND MNEMONIC SECURITY - IVANGORODSKY, Kostiantyn (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to identify the main directions of memorial legislation development in Eastern European countries at the present stage, in particular, in the context of determining its functioning in the coordinates of the ethnopopulist rhetoric growth of the respective political regimes and clarifying the degree of mnemonic security, which we could come across in the memorial legislation. Scientific Novelty. Regarding the idea that memory management in contemporary politics has important ramifications for the retreat from democracy, the Eastern European region offers food for thought. At the same time, the analysis of the Russian, Polish and Ukrainian legislative regulation of historical memory emphasizes that the “wars of memory” are unfolding as proxy wars for modern state identities and the sense of the states security as actors of a special kind. Eastern Europe has become the “main laboratory” for studying the interrelationships between law and memory since the mid-2000s. Memory wars have broken out in the Russian-Ukrainian-Polish triangle, and historical politics, including memory laws, have become the weapon that regimes consciously relied on in their propaganda. The countries in the region have struggled for the mnemonic acknowledgment in the global social hierarchy of remembrance of the major historical events, as evidenced by their memorial laws. Conclusions. Due to determining the main directions of functioning in the mnemonic space of Europe regarding memory laws in the countries of its eastern part, it is feasible to bring up their striking difference from the generally accepted policy of memory in the EU. The tangible ethno-populist rhetoric is considered to be one of the controversial issue, which is inherent in such memorial legislative acts. On the other hand, the example of modern Ukraine, which is in a state of fierce and hostile war with Russia, allows us to realize the powerful potential of the mnemonic security of such legislation more deeply. Key words: Eastern Europe, memorial legislation, memory laws, historical politics, historical memory, ethno-populism, mnemonic security.